(untitled) - Bundesarbeitsgemeinschaft der Freien Wohlfahrtspflege e. V. (Sozialwirtschaft aktuell (SWa), 2024)
The journal Sozialwirtschaft aktuell informs its readers quickly and concisely about new developments in the field of socio-economics. It focuses on essential information and comments on political, professional, legal and tax-related topics. In addition to short expert contributions, it provides announcements and corporate news. Its useful tips, personal details and notifications of events ensure the reader feels well informed at all times. Sozialwirtschaft aktuell will appeal to the executive boards and managing directors of charity organisations, associations, action groups and facilities; managers of social services facilities; those working in the higher echelons of administrative bodies and organisations; consultants; academics; trainees and those on further training programmes.